Building Customer Relationship Management through Digital Marketing Communication Strategies in GO-JEK Indonesia - Nanda, Mutya; Praptiningsih, Novi Andayani; Hayat, Heni; Amallah, Nurlalillah Sari (Communicare : Journal of Communication Studies, 2025)
This study examines how PT Go-Jek Indonesia implements marketing communication strategies through digital Customer Relationship Management (CRM) to strengthen customer relationships. The research aims to identify Go-Jek’s digital CRM activities, innovations in relationship building, and the obstacles and benefits of using digital CRM. The theoretical foundation is the Integrated Marketing Communication (IMC) theory, and the study employs a qualitative case study approach to provide an in-depth understanding of Go-Jek’s marketing communication strategy. Data were collected through in-depth interviews and analyzed descriptively, employing data reduction, presentation, and drawing conclusions. The findings reveal that Go-Jek’s digital CRM activities are conducted through three main stages: acquisition, enhancement, and retention. These involve building customer databases, profiling, profitability analysis, and interactive engagement using six IMC elements: advertising, sales promotion, events and sponsorships, publicity, direct marketing, and interactive marketing. Go-Jek’s main breakthrough lies in utilizing big data to analyze customers and partners individually, enabling personalized marketing communication. However, obstacles remain in several marketing mix components, particularly in product, price, and place. Despite these challenges, digital CRM provides significant benefits, including increased communication efficiency, reduced costs, and improved ability to evaluate and optimize organizational performance.